Thematic Scientific Bibliography as a Discourse: Modern Youth Values - M. A. Eremina (Научный диалог)
The experience of collecting and systematizing scientific sources from different humanitarian fields, united by a common theme — values in the modern youth environment are described in the article. This content brings the article closer to the genre of an interdisciplinary bibliographic review. The practical task of the review is to prepare a bibliographic reference manual for publication. The selection of scientific publications was based on key axiological concepts, as well as on the idea of youth as a demographic and sociocultural group of people from 14 to 30 years old, on the way to becoming psychophysiological maturity and socialization. Conclusions of a theoretical nature are connected with the identification of general patterns of development of youth axiological issues: consideration of values within the framework of individual types (moral, political, religious, family, etc.); the predominance of works devoted to the study of the mutual influence of values and the sociocultural environment; the predominant interest of scientists in the study of spiritual, moral and socio-political values; the tendency of the last 5 years to highlight the values of communication and information as an independent object of axiological research. The practical task of compiling a bibliographic manual is solved in the form of determining the main principle of rubrication, which is the subject-thematic (typological) approach.